The Comparison of the Gut Microbiome Composition, Serum Inflammatory Markers and Faecal Short‐Chain Fatty Acids Among Individuals With Type 1 and 2 Diabetes Mellitus With Healthy Controls: A Case–Control Study - Hossein Yarmohammadi; Masood Soltanipur; Mahdi Rezaei; Hanieh‐Sadat Ejtahed; Maedeh Raei; Alireza Razavi; Seyed Mohsen Mirhosseini; Mehrangiz Zangeneh; Delaram Doroud; Abolfazl Fateh; Seyedalireza Seyed Siamdoust; Seyed Davar Siadat (Endocrinology, Diabetes & Metabolism, 2025)
ABSTRACT Background This study aimed to compare the gut microbiome (GM) composition, serum inflammatory markers and faecal short‐chain fatty acids among individuals with type 1 and type 2 diabetes mellitus (DM) and healthy controls. Methods This case–control study examined 49 subjects with type 2 DM, 21 with type 1 DM and 40 healthy controls. Blood and faecal samples were collected. Serum inflammatory markers, including CRP, IL‐1β, IL‐6, TNF‐α and IFN‐γ, were measured using enzyme‐linked immunosorbent assays (ELISA). Bacterial populations were quantified using RT‐qPCR and NGS. Faecal metabolites were analysed using gas chromatography. Results Simpson's alpha diversity was higher among types 1 and 2 DM than in the control. The frequency of the bacterial genera Gemmiger, Dorea, Collinsella, Escherichia/Shigella, Dialister, Coprococcus, Achromobacter, Intestinimonas and Allisonella in type 2 DM was higher than in the control, and the frequency of the genera Romboutsia and Clostridium was decreased in type 2 DM. The frequency of the Prevotella, Bacteroides and Faecalibacterium genera in type 1 DM was lower than in the other groups. Acetate, propionate and butyrate levels were significantly higher in type 2 DM patients compared to the other groups. Participants with diabetes had significantly higher hs‐CRP, IL1‐β, TNF, IL‐6 and IFG levels compared to the controls. Compared to healthy controls, both T1DM and T2DM patients showed a significant increase in the abundance of the Lactobacillus genus (p = 0.01) and a decrease in Faecalibacterium (p = 0.02). Additionally, serum levels of IL‐6 and TNF‐α were significantly elevated in T2DM patients (p = 0.003 and p = 0.005, respectively). Faecal levels of butyrate were significantly reduced in both diabetic groups compared to the controls (p = 0.004). Conclusion By determining the GM alterations in patients with diabetes, interventional strategies could be designed to modulate the GM composition as an adjunctive therapy in diabetes.